Pendidikan Peningkatan Pengetahuan Siswa Tentang Tanggap Bencana di SMK SPP Snakma Muhammadiyah - Anan Rizky; Yuni Suharnida Lubis; Nadya Ulfa Kesumawardani (STIKES Columbia Asia Medan, 2024)
In essence, every child has the right to safety, survival, and the right to receive quality education. However, these rights may not be fulfilled due to several threats, both internal and external. Threats can occur from family factors, the environment, nature, and technology that can cause children's rights to be unsustainable. These disasters, both small and large disasters, will basically have an impact on the safety and education of children. If education is disrupted, there is a risk that children will drop out of school or even be unable to attend school permanently. The interruption of education will have a negative impact on children both economically and socially in the future, in addition to also having an impact on the child's family and community.